2000 m rowing ergometer performance increases oxidative stress in well-trained rowers - Nikolaidis, M.; Kyparos, A.; Vrabas, I.; Riganas, C.; Kouretas, D. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
High intensity and long duration exercise is related to increased oxidative stress. Competition level rowing is very demanding requiring maintenance of high power mostly produced from aerobic metabolism. The aim of this study was to investigate whether or not an all-out 2000 m rowing race simulation test could induce oxidative stress, as assessed by selective oxidative stress markers. A total of 22 (19 male and 3 female) highly-trained national level rowers volunteered to participate in this study (Mean ± SEM, age: 18.1±0.8 yrs, training age: 5.4±0.6 yrs, weight: 76.3±2.8 kg, height: 177.7±1.8 cm, BSA: 1.9±0.04 m2). Following an overnight fast, blood samples were taken from an antecubital vein before and immediately after the termination of a 2000 m all-out effort on a wind resistance braked rowing ergometer (Concept IIc, Nottingham, UK). To simulate race conditions and enhance motivation, athletes performed the test in pairs competing with each other. The blood samples obtained were used for the determination of selective oxidative stress markers. Whole blood lysate reduced (GSH) and oxidized (GSSG) glutathione, as well as serum thiobarbituric acid-reactive substances (TBARS), protein carbonyls, catalase and total antioxidant capacity (TAC) were measured as previously described (Nikolaidis et al., 2007). Post-exercise plasma volume changes were corrected according to Dill & Costill (1974). All procedures were in accordance to the guidelines set by the American College of Sports Medicine on research with human subjects. Data were analyzed using paired Student`s t test (P<0.05). Mean time for the 2000 m trial (T2000) was 416.8±5.5 s; Power (P2000) 315.3±11.2 w; Strokes per minute (SPM2000) 29.5±0.2 strokesmin-1; Energy expenditure (EE2000) 158.8±2.5 cal; Time average every 500 m (T500) 1.46±0.03 min; and Heart rate (HR2000) 197.7±0.9 beatsmin-1. Post-exercise GSSG concentration significantly increased (pre 0.06±0.01 vs. post 0.08±0.01 mM, P=0.004), whereas GSH concentration remained unchanged (0.51±0.03 vs. 0.48±0.03 mM, P>0.05), resulting in an overall decreased post-exercise GSH/GSSG ratio (9.5±2.0 vs. 6.8±0.9, P=0.01). Post-exercise TBARS concentration (4.04±0.4 vs. 5.97±0.4 956;M, P<0.001) and protein carbonyls (0.42±0.02 vs. 0.72±0.04 nmol/mg protein, P<0.001) increased as compared to the pre-exercise levels. Likewise, post-exercise catalase activity (13.4±1.2 vs. 27.2±3.4 mmol/L/min, P<0.001) and TAC (0.67±0.01 vs. 0.73±0.01 mM DPPH, P<0.0001) significantly increased. We conclude that a 2000 m rowing ergometer race induces significant blood oxidative stress in highly fit rowers. In the light of the potential implications that excessive oxidative stress may impose in athletic performance and health, it is important that high caliber